2019
DOI: 10.1021/acs.est.9b01939
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Lattice Oxygen in LaFe (Oxy)hydroxides for Efficient Phosphorus Removal

Abstract: Lanthanum (La)-based materials have been recognized as promising adsorbents for aqueous phosphate removal. The incorporation of base metals into La (oxy)­hydroxides represents an effective strategy to improve adsorption performance. Understanding how base metals affect phosphate adsorption is challenging but essential for the development of effective materials for phosphorus control. Herein, we demonstrated a high-performance LaFe (oxy)­hydroxide and studied its mechanisms on phosphate adsorption. The P K edge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 118 publications
(41 citation statements)
references
References 34 publications
3
38
0
Order By: Relevance
“…As illustrated in Fig. S3, it is common sense for us that broad vibration bands located at 3433 and 1634 cm − 1 are observed for all materials, which can be ascribed to the stretching vibration of adsorbed water molecules and the bending vibration of the -OH group, respectively (Wang et al 2020, Yu et al 2019. As shown in Fig.…”
Section: Ftir Analysismentioning
confidence: 76%
See 4 more Smart Citations
“…As illustrated in Fig. S3, it is common sense for us that broad vibration bands located at 3433 and 1634 cm − 1 are observed for all materials, which can be ascribed to the stretching vibration of adsorbed water molecules and the bending vibration of the -OH group, respectively (Wang et al 2020, Yu et al 2019. As shown in Fig.…”
Section: Ftir Analysismentioning
confidence: 76%
“…For the tplot micropore area and average pore volume, the Fe-La binary (hydr)oxides showed similar trends with changes in the Fe/La ratios. These observations indicated that the incorporation of Fe and La metals on the Fe/La 1:1 (hydr)oxides was different from that of the other two type Fe-La (hydr)oxides (Yu et al 2019). However, the average pore diameters were 35.2, 103.3 and 192.8 Å for the Fe/La 3:1, Fe/La 1:1 and Fe/La 1:3 (hydr)oxides, respectively, and increased with the increase in La contents, which may be attributed to the change of the particle shape from irregular and aggregated particles to nano akes, as observed by SEM in Fig.…”
Section: Speci C Surface Areamentioning
confidence: 81%
See 3 more Smart Citations